(untitled) (Siddhajyoti Interdisciplinary Journal, 2025)
Nutrition plays a pivotal role in shaping every individual’s cognitive, affective and psychomotor domains. One of the most important markers of one’s general health is one’s nutritional status. The most active stage of a child’s growth occurs during school age. Kinds of literature shows that childhood malnutrition is one of the main reasons why child mortality rates are greater in developing countries. People’s quality of life is negatively impacted by chronic malnutrition in children, which has been associated with delayed cognitive development and serious health issues later in life. It is thought that the Tharu community faces social and economic disadvantages. Therefore, the goal of this study is to assess the nutritional status of children under five in Nepal’s Dang District within the Tharu community. It employed a quantitative research design involving 200 randomly selected households. Each household contributed one child for anthropometric evaluations, while mothers provided data on their children’s food habits. The findings revealed important levels of underweight and low BMI, alongside average or overweight rates, indicating poor nutritional status among the children. Policymakers and healthcare professionals can use this research as a valuable reference to enhance maternal and child health outcomes in Nepal.